2017
DOI: 10.12973/ejmste/81149
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Using Collaborative Tools on the Community of Inquiry in an Interdisciplinary Project-Based Learning Context

Abstract: This study aims to explore the relationships among three presences, namely cognitive presence, social presence and teaching presence in a Community of Inquiry (CoI) framework in the context of interdisciplinary project-based learning (IPBL) through the collaborative technology Google Applications. The survey data was collected from 138 students with mixed subject specialism participated in a cultural creativity project. All participants were randomly assigned into one of two groups. The control group used onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…With the widespread proliferation of Web 2.0 technologies, more collaborative virtual spaces such as Google Applications, blogs, wikis and forums were developed to facilitate goal-oriented activities and task-specific interactions (Cheung & Vogel, 2013). According to Hsu and Shiue (2018) online collaborative environments provide a common platform that allows students to discuss, share and exchange ideas; interact with their peers, instructors and the content; co-construct knowledge and develop a sense of belonging to a learning community. As learning occurs as a result of social interactions (Vygotsky, 1978) and collaborative technologies afford enriched learning activities and increased participation, Ishtaiwa and Aburezeq (2015) further that collaborative tools improve academic success and performance.…”
Section: Collaborative Online Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the widespread proliferation of Web 2.0 technologies, more collaborative virtual spaces such as Google Applications, blogs, wikis and forums were developed to facilitate goal-oriented activities and task-specific interactions (Cheung & Vogel, 2013). According to Hsu and Shiue (2018) online collaborative environments provide a common platform that allows students to discuss, share and exchange ideas; interact with their peers, instructors and the content; co-construct knowledge and develop a sense of belonging to a learning community. As learning occurs as a result of social interactions (Vygotsky, 1978) and collaborative technologies afford enriched learning activities and increased participation, Ishtaiwa and Aburezeq (2015) further that collaborative tools improve academic success and performance.…”
Section: Collaborative Online Technologiesmentioning
confidence: 99%
“…Asynchronous communication is also possible and as well different versions of ideas can be monitored and tracked (Lin et al, 2016). Indeed, empirical research has revealed various educational benefits of using online collaborative technologies in learning environments such as enhancing motivation (Lin et al, 2016), increasing the learning of content knowledge through social interactions (Hsu & Shiue, 2018) and facilitating the interplay between the elements of collaborative online learning settings identified by Curtis and Lawson (2001) as learner-instructor, learner-learner, learner-content, and learner-interface interactions (Ishtaiwa & Aburezeq, 2015). Farrell (2008) indicates that working collaboratively on problematic cases can engage learners in productive interactions and introduce them to many and varied perspectives.…”
Section: Collaborative Online Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Russian and foreign scientists, in particular, S. V. Ivanova, L. S. Pastukhova [7], A. P. Kazun, L. S. Pastukhova [8], Y.C. Hsu, Y. M. Shiue [28], L.A. Jacques [30], non-systemic and fragmented project activities can seriously slow down the effective implementation of the project method. We plan and organize the project activities of environmental students in such a way that the object is studied comprehensively as a result of not just one, but a whole sequence of projects where each subsequent result has scientific novelty and deepens the knowledge gained in the previous step.…”
Section: Resultsmentioning
confidence: 99%
“…Collaborative learning technologies are believed to build up knowledge and promote meaningful interactions among learners (Hsu & Shiue, 2018). It allows students to actively participate and work together to attain a common goal (Lutakova & Antala, 2017).…”
Section: Introductionmentioning
confidence: 99%